The entrepreneurial process and economic success in a constrained environment - Kodithuwakku, Sarath S; Rosa, Peter (Journal of Business Venturing, 2002)
The nature and impact of the entrepreneurial process on economic and business success is difficult to research as there are many intervening variables to consider. It is also a complex ongoing evolutionary process, which can only be fully understood in the context of the wider socioeconomic environment. Conventional cross-sectional quantitative approaches can only provide limited insights and answers on the entrepreneurial process. This paper explores the role of the entrepreneurial process in the economic and business success of Sri Lankan villagers. The setting is especially favourable for the study of entrepreneurial processes, as it approximates to a “natural experiment” in which many normal intervening variables are controlled for. Families with no previous assets were settled on two and a half acres of land in 1984. From equal beginnings, the village had polarised 10 years later into a majority of economically unsuccessful villagers, and a small but influential and successful entrepreneurial class. An ethnographic and multiple-embedded case study approach was adopted to explore their success. The economically unsuccessful villagers had entered a cycle of impoverishment, rapidly running into debt, many losing control of their allocated paddy lands, and having to become wage labourers to make a living. The successful entrepreneurs in contrast had accessed a surprising range and combination of economic opportunities, and had started multiple ventures (an average of 3.7 each). The findings reveal that entrepreneurial processes were important in the successful entrepreneurs' emergence from an extremely unpromising and constrained environment. In achieving success, they were not much more innovative in identifying opportunities than the unsuccessful villagers. Rather, they were much more creative and persistent in finding ways to mobilise scarce resources. In particular, their ability to extract value from their social networks and contacts was a vital element in their struggle to accumulate more capital. The successful entrepreneurs were also adept at efficiently managing their enterprises, a factor that became increasingly important as pluriactivity increased. This supported the argument that both entrepreneurship and management are necessary for business success, and that they are interdependent and complementary. As most economic environments are significantly resource-starved, the paper provides insights for other researchers on how to approach the study of entrepreneurial processes in such environments.